The Concept of ,,Lean“ Production Management and Value Creation System - Statkus, Justinas (Jaunųjų mokslininkų darbai, 2018)
One of the means for continuous improvement of quality is the implementation of “Lean” system. The purpose of this article is to reveal the essence of the “Lean” system, analyse its benefits in activities of different organizations. The efficiency of the system has been confirmed by experience of many companies. Improvements of the system in past decades and variety of methods used makes it useful and favoured by users. In scientific literature “Lean” is considered as philosophy of management – a system of production and management. The purpose of the system is to minimize volumes of work, which is considered a loss, and in turn to increase the amount of added-value work. An organization‘s management system must be evaluated to determine if it meets the requirements of the “Lean” system, identifying the need for implementation.  As a result, such a system can be implemented in any company. This can be based on examples from various companies. The article discusses the implementation of the “Lean” system in a public catering company, a bank and even in a specialized personal health care institution.
Keywords: “Lean” system; efficiency; management